Strategy Formulation in A Microenterprise: Case Study SEHATEA Ice Tea - Sopiawadi, Mutqi; Lugiani, Tigin (Publisher Cv. Inara Colaboration with www.stie-sampit.ac.id, 2024)
This research aims to examine and analyze the environmental conditions, conduct a SWOT analysis, and design a strategy formulation and implementation through the EFAS IFAS method. One of the scopes is within the Micro, Small, and Medium Enterprises (MSMEs) of SEHATEA Iced Tea, which has become a new business that is highly sought after by both young people and adults and has high business potential. The qualitative study conducted at Sehatea Iced Tea resulted in a SWOT analysis and matrix that outlines the vision, mission, and strategy. After conducting a SWOT analysis on Sehatea MSMEs in the Subang district, it was found how the external and internal conditions of these Sehatea MSMEs are. Sehatea will face greater opportunities compared to threats, while from the external conditions and the internal conditions of MSMEs, they have more strengths than weaknesses. From the results of the SWOT matrix analysis, the Vision, Mission, strategic objectives, and strategies of Sehatea MSMEs in the Subang district were born, based on the SWOT matrix analysis, the vision is to make Sehatea Iced Tea the No. 1 Iced Tea Brand in Subang at an affordable price. To achieve this vision, Sehatea MSMEs strive to provide products with good quality and affordable prices. To realize the existing vision, a mission is designed, namely, standardized product quality with a halal label, maintaining financial performance, creating product innovation, competent human resources in work, and expanding the network of potential consumer markets and businesses.